LANDASAN TEOLOGIS DAN FILOSOFIS AQIDAH AKHLAK DALAM PERSPEKTIF AL-QUR’AN, SUNNAH, AKAL, DAN REALITAS SOSIAL - Fitri Handayani; Eka Putra Wirman; Hasnah (As-Sulthan Journal of Education, 2026)
This article examines the theological and philosophical foundations of aqidah and akhlaq within the perspective of Islamic education through the integration of four fundamental elements: the Qur’an, the Sunnah, reason, and social reality. Aqidah is positioned as a transcendental foundation of faith, while akhlaq is understood as the ethical manifestation of belief in both personal and social life. This study employs a qualitative approach using a library research method. The findings indicate that the Qur’an functions as the primary theological source, the Prophet’s Sunnah serves as a practical exemplar, reason operates as a philosophical instrument of reflection, and social reality provides the arena for the actualization of aqidah and akhlaq values. The integration of these four elements underscores the relevance of aqidah and akhlaq in addressing contemporary moral challenges and contributes to the development of a holistic and contextual Islamic education.